Challenges in implementing India’s Aadhaar-enabled fertilizer management system - Singh, Vartika; Ward, Patrick S.; International Maize and Wheat Improvement Center; International Rice Research Institute (International Food Policy Research Institute, 2018)
The Government of India has introduced what is commonly referred to – albeit incorrectly – as a Direct Benefit Transfer (DBT) scheme for fertilizers. One of the primary motivations behind DBT for fertilizers is that it would enable better monitoring of transactions of heavily subsidized fertilizer across the country. Digitizing purchases would also allow inventories to be managed better and the system’s demand prediction ability to be improved, given that most of the annual demand is concentrated into 3–4 months....This evaluation of the implementation processes across the states of Bihar, Odisha, and Uttar Pradesh provides an opportunity to make significant recommendations and feedback to policy makers and implementers at the state and central level to influence and enhance its chances for success.